Boundary Crossing in a Professional Association: The Dynamics of Research Use Among State Leaders and Researchers in a Research-Practice Partnership. (December 2019) - Hopkins, Megan; Weddle, Hayley; Gluckman, Maxie; Gautsch, Leslie
As spaces for researchers and practitioners to engage in long-term, mutual collaborations aimed at addressing problems of practice in education, research-practice partnerships (RPPs) offer rich contexts for research use. Our study examines how interactions between researchers and practitioners shape opportunities for research use in a professional association engaged in RPP activities focused on fostering change in statewide K–12 science education. Drawing on a conceptualization of RPPs as joint work at boundaries, we show how both researchers and practitioners facilitated research use. Furthermore, research use was facilitated by brokers' engagement in RPP activities and with shared pieces of research. Findings affirm the role that brokers play in connecting research and practice and identify specific activities that may be useful in facilitating research use in RPPs.